A data readout approach for physics experiments*Supported by National Natural Science Foundation of China (11005107) and Independent Projects of State Key Laboratory of Particle Detection and Electronics (201301). (July 2015) - Huang 黄, Xi-Ru 锡汝; Cao 曹, Ping 平; Gao 高, Li-Wei 力为; Zheng 郑, Jia-Jun 佳俊
Abstract: With increasing physical event rates and the number of electronic channels, traditional readout schemes meet the challenge of improving readout speed caused by the limited bandwidth of the crate backplane. In this paper, a high-speed data readout method based on the Ethernet is presented to make each readout module capable of transmitting data to the DAQ. Features of explicitly parallel data transmitting and distributed network architecture give the readout system the advantage of adapting varying requirements of particle physics experiments. Furthermore, to guarantee the readout performance and flexibility, a standalone embedded CPU system is utilized for network protocol stack processing. To receive the customized data format and protocol from front-end electronics, a field programmable gate array (FPGA) is used for logic reconfiguration. To optimize the interface and to improve the data throughput between CPU and FPGA, a sophisticated method based on SRAM is presented in this paper. For the purpose of evaluating this high-speed readout method, a simplified readout module is designed and implemented. Test results show that this module can support up to 70 Mbps data throughput from the readout module to DAQ.